Molecular cloning and functional characterization of BcTSA in the biosynthesis of indole alkaloids in Baphicacanthus cusia - Guo, Zhiying; Chen, Junfeng; Lv, Zongyou; Huang, Yuxiang; Tan, Hexin; Zhang, Lei; Diao, Yong (Frontiers in Plant Science, 2023)
Baphicacanthus cusia (Nees) Bremek (B. cusia) is an essential traditional Chinese herb that is commonly used to treat colds, fever, and influenza. Indole alkaloids, such as indigo and indirubin, are the primary active constituents of B. cusia. The indole-producing reaction is crucial for regulating the flow of indole alkaloids metabolites along the pathways and coordinating primary and secondary product biosynthesis in plants. The tryptophan synthase alpha-subunit (TSA) can catalyse a process that produces indole, which is free to enter secondary metabolite pathways; however, the underlying potential mechanism of regulating indigo alkaloids synthesis remains unknown. Here, a BcTSA was cloned from the transcriptome of B. cusia. The BcTSA has a significant degree of similarity with other plant TSAs according to bioinformatics and phylogenetic analyses. Quantitative real-time PCR (RT-qPCR) research showed that BcTSA was dramatically enhanced in response to treatment with methyl jasmonate (MeJA), salicylic acid (SA), and abscisic acid (ABA), and was predominantly expressed in the stems as opposed to the leaves and rhizomes. Subcellular localization revealed that BcTSA is localized in chloroplasts, which is compatible with the fact that the conversion of indole-3-glycerol phosphate (IGP) to indole occurs in chloroplasts. The complementation assay results showed that BcTSA was functional, demonstrating that it was capable of catalyzing the conversion of IGP to indole. BcTSA was shown to stimulate the manufacture of indigo alkaloids including isatin, indigo, and indirubin when the gene was overexpressed in the hairy roots of Isatis indigotica. In conclusion, our research provides novel perspectives that might be applied to manipulating the indole alkaloid composition of B. cusia.